Kosmos : jewellery, adornment and textiles in the Aegean Bronze Age : proceedings of the 13ᵗʰ international Aegean conference / 13ᵉ rencontre égéenne internationale, University of Copenhagen, Danish National Research Foundation's Centre for Textile Research, 21-26 April 2010 (Leuven ; Liège)
x, 810 sayfa, clxxxv sayfa resim
Keywords: “The subject of KOSMOS in the Aegean Bronze Age includes jewellery, costume, aesthetics, body adornment, colours, pigments, and textiles. The reason for this choice of subject was our wish to merge the textile research carried out currently at the Danish National Research Foundationís Centre for Textile Research, with the major research topic of Robert Laffineur, jewellery. This KOSMOS volume addresses the issues of textile production, costumes, dyes and pigments, colours, jewellery, aesthetics, body adornment, luxury and exotic items, gender and femininity/masculinity, as well as their social, religious, ideological, economic, technological, administrative and philological connections. In the Bronze Age, men, women and children would dress in garments, wear jewellery and adorn themselves to express their gender, age and status.” --